Emotion Pedagogies: What Are They, and Why Do They Matter?. (June 2016) - Wilce, James M.; Fenigsen, Janina
Abstract: This introductory essay defines "emotion pedagogies" by identifying their distinctive qualities—an inclusive embrace of emotions often presented in the form of lists of emotion words to be spoken as part of "I‐messages;" treating emotions as teachable skill bundles, like other sets of skills conveyed along the model of formal schooling and thus involving a high degree of curricularization; and finally, the spread of emotion pedagogies as reflections and facilitators of Charles Taylor's "subjective turn, " Foucault's "subjectification, " and a unique self‐managed and self‐responsible neoliberal selfhood. We introduce each of the articles in this special issue and conclude with reflections on the transformative potential of emotion pedagogies. Tassä artikkelissa "tunnepedagogiikat" (emotion pedagogies) määritellään ilmiöksi, jonka ominaislaatuihin ja tavoitteisiin kuuluvat 1) tunteiden kattava hyväksyminen esimerkiksi tunnesanalistan avustamana, joita voidaan kayttää myös osana "minä‐viestejä" ja 2) tunteiden käsittäminen taitoina, joita voi oppia ja opettaa muodollisessa koulutuksessa kuten muitakin taitoja. Tunne‐pedagogiikkojen leviamistä ja suosiota käsitellään Charles Taylorin subjektiivisen käänteen ja Foucault'n subjektifikaation näkökulmista sekä heijastumina neoliberaalista tavasta nähdä minus uniikkina ja itsen päätöksistä riippuvaisena. Johdannossa esitellään myös kaikki erikoisnumeron artikkelit, ja lopuksi pohditaan tunnepedagogiikkojen transformatiivista potentiaalia.